(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: The plant is reported to have multiple therapeutic properties such as chronic subclinical inflammation. Objective: In this present study Aegle marmelos was investigated for its anti-inflammatory effects on human T2DM subjects. Methodology: The present study was conducted at Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka, Bangladesh from July 2010 to June 2011 to explore the effect of Aegle marmelos unripe fruit pulp on chronic subclinical inflammatory status in T2DM patients as evident by hsCRP. It was an un-blinded clinical trial conducted under a cross-over design. The experiment was conducted under a crossover design and the effects were analyzed during the 0-21 as well as 28-49 days with 7 days wash out period. The data were then pooled and the baseline versus endpoint values was also compared. Result: The mean blood hsCRP values did not significantly differ between the intervention and control groups at any time points. No significant difference between the baseline and end point values regarding blood hsCRP. The effect on blood hsCRP was not significant in any of the analysis. Conclusion: This study reveals no changes in chronic subclinical inflammatory status of Aegle marmelos fruit pulp in T2DM patients. Journal of Current and Advance Medical Research, January 2021;8(1):17-20